Pengembangan E-Book DNA Sekuensing untuk Berpikir Kritis dan Literasi Lingkungan - Dwi Fitriany Hanafi; Hanum Isfaeni; Rusdi (Postgraduate, University of Mataram, 2025)
This study aims to develop a Bio-Genetics Ebook based on In Silico DNA Sequencing and analyze its influence on critical thinking and environmental literacy of grade X students at SMA Negeri 30 Jakarta. The learning media in the form of an ebook produced examines and analyzes populations and species by utilizing computing technology in the form of DNA sequencing using NCBI in DNA analysis and Mega to obtain a phylogenetic tree. The student needs analysis stage revealed that students need interactive learning media that is easy to carry anywhere. The design stage produced an ebook design with superior content of in silico DNA sequencing, bioinfo, case studies, and quizzes. From the results of the media and material feasibility test carried out at the development stage, the results were 84% and 89% respectively. The ebook was considered suitable for use and only required minor adjustments. Educators and students evaluated the small group trial, with scores of 84% and 82% respectively, indicating that the trial could be used as a biology learning medium. The use of In Silico DNA Sequencing-based Bio-Genetics Ebook on critical thinking skills and environmental literacy of students has increased, according to the results of the MANOVA hypothesis test which also showed a significance value of 0.00 <0.05. Thus, the developed ebook is suitable for use as a biology learning medium and to improve critical thinking skills and environmental literacy of students.